THE EFFECT OF TOMATO (Lycopersicum esculentum Mill) TO AMOUNT, MOTILITY, AND MORPHOLOGY OF SPERMATOZOA IN CIGARETTES-INDUCED INFERTILTY PATIENTS - Prayoga, Prianggara Rostu (Majority, 2015)
The data from BKKBN (2011) shows the case precentage of infertility that caused by man is same as the woman. The effect that occurs is infertility and can cause a major problem in the family. The cigarettes can cause problem in male reproduction system such as infertility caused by the free radicals that the cigarettes produces. To overcome this problem, the body need more antioxidant besides the one that our body produces. One of the fruit that contains antioxidant is tomato. Research from India shows that man who consumed food with rich lycopene, such as tomato, will increased the amount, repairs the structures, and motility of the sperm. Tomato attract many attention because of the red pigment of the tomato, lycopene, known as one of the strongest antioxidant. The substances in tomato that works as an antioxidant is not just the lycopene, but there is other substances such as vitamin C and flavonoid. The main function of antioxidant to againts the free radicals is giving the hidrogen atom, known as primary antioxidant. The secondary function, known as secondary antioxidant, is to slowdown the rate of autooxidation with some mechanism than the mechanism that breaks the chain of autooxidant by changing the lipid radicals to some more stable form. Tomato had the effect to increased the amount, motility, and morphology of the spermatozoa in cigarettes-induced infertility patients. The substances in tomato, like lycopene, could used as strong antioxidant to againts free radicals with the mechanisms of its primary and secondary functions. Keywords: antioxidant, cigarettes, free radicals, infertility, man, tomato Abstrak Data BKKBN (2011) menunjukkan kasus infertilitas yang disebabkan oleh pihak pria persentasenya sama seperti pada wanita. Dampak yang ditimbulkan bagi beberapa orang adalah tidak kunjung mendapatkan keturunan dan dapat menjadi masalah serius di dalam keluarga. Rokok pada sistem reproduksi pria dapat mengakibatkan infertilitas akibat radikal bebas yang dihasilkan. Untuk mengatasi hal tersebut maka tubuh membutuhkan asupan antioksidan dari luar tubuh. Salah satu tanaman buah yang mengandung senyawa antioksidan adalah tomat. Penelitian di India menyatakan bahwa pria yang mengkonsumsi makanan yang kaya likopen seperti tomat akan meningkatkan jumlah, memperbaiki struktur dan kegesitan sperma. Tomat menarik banyak perhatian sejak diketahui bahwa pigmen merah pada tomat, likopen, disebut sebagai salah satu antioksidan paling kuat di dunia. Zat dalam tomat yang bekerja sebagai antioksidan tidak hanya likopen, namun terdapat zat lain seperti vitamin C dan flavonoid. Fungsi utama dari antioksidan dalam melawan radikal bebas yaitu sebagai pemberi atom hidrogen dan disebut sebagai antioksidan primer. Fungsi kedua merupakan fungsi sekunder antioksidan, yaitu memperlambat laju autooksidasi dengan berbagai mekanisme diluar mekanisme pemutusan rantai autooksidasi dengan pengubahan radikal lipida ke bentuk lebih stabil. Tomat memiliki efek terhadap peningkatan jumlah, motilitas, dan morfologi spermatozoa pada pria yang mengalami infertilitas akibat rokok. Kandungan yang terdapat dalam tomat seperti likopen dapat digunakan sebagai antioksidan kuat untuk melawan radikal bebas dengan mekanisme kerja sesuai dengan fungsi primer dan sekundernya. Kata Kunci: antioksidan, infertilitas, pria, radikal bebas, rokok, tomat